The Effect of Academic Supervision of School Principles and Teachers’ Performance Satisfaction in Increasing Teachers’ Pedagogical Competence - Nurhayati, Nurhayati; Mesiono, Mesiono; Daulay, Nurika Khalila (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the effect of the principal's academic supervision and teacher performance satisfaction on improving the pedagogic competence of teachers in PAB schools, Deli Serdang Regency. This type of research is quantitative with a survey method involving teachers. The data was collected by means of observation, questionnaires, and documentation. Data analysis used instrument validity and instrument reliability. The results of hypothesis testing have a positive and high relationship between the principal's academic supervision and teacher job satisfaction together with the teacher's pedagogic competence. The magnitude of the effect is indicated by the coefficient of determination R2 (R square) = 0.431, meaning that the principal's academic supervision and teacher job satisfaction together have an influence on the teacher's pedagogic competence of 43.1% and the remaining 56.9% is determined by other factors. The results of simple regression analysis show the equation = 32.725 + 0.190X1 + 0.567X2.